Perilaku Harian Buaya Muara (Crocodylus porosus, Schneider 1801) di Pusat Penyelamatan Satwa Jogja - I., Purwo Setio; Muharromi, A. Fanani; Prihantono, Subekti; Qurniawan, Tony Febri; Nugraha, A. Prima; Eprilurahman, Rury (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
The aim of this research was to find out the daily behaviour of Crocodylus porosus in Jogja Animal Rescue Center (PPSJ). The daily behaviour included feeding habit, social behaviour, basking and movement. This research was using Focal Animal Sampling Method and observed for four months. As individual targets were male and female dominant of C. porosus, Monti and Bunda. The Runs test showed that the behavior of C. porosus had a pattern in daily activities. Based on Mann-Whitney U test, both male and female of C. porosus did not have any difference in feeding habit (U=16; n1= 6; n2=6; p>0,05), social behaviour (U=29; n1= 8; n2=8; p>0,05), basking (U=12; n1= 5; n2=5; p>0,05) and movement (U=16; n1= 6; n2=6; p>0,05).